2012
DOI: 10.1099/mic.0.059469-0
|View full text |Cite
|
Sign up to set email alerts
|

MaHog1, a Hog1-type mitogen-activated protein kinase gene, contributes to stress tolerance and virulence of the entomopathogenic fungus Metarhizium acridum

Abstract: Fungal biocontrol agents have great potential in integrated pest management. However, poor efficacy and sensitivity to various adverse factors have hampered their wide application. In eukaryotic cells, Hog1 kinase plays a critical role in stress responses. In this study, MaHog1 (GenBank accession no. EFY85878), encoding a member of the Hog1/Sty1/p38 mitogenactivated protein kinase family in Metarhizium (Me.) acridum, was identified. Targeted gene disruption was used to analyse the role of MaHog1 in virulence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 55 publications
(51 reference statements)
3
48
0
Order By: Relevance
“…Our results indicated that PfHog1 is an important regulator of osmotic tolerance in P. fijiensis , similar to previous reports on other filamentous fungi and yeasts (Beever and Laracy, 1986; Schuller et al, 1994; Jin et al, 2012; Babazadeh et al, 2013; Wang et al, 2016). The growth and development of mycelia fragments of Δ PfHog1 mutants were suppressed on PDA medium supplemented with 1 M NaCl; whereas WT P. fijiensis showed normal growth and development of mycelia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicated that PfHog1 is an important regulator of osmotic tolerance in P. fijiensis , similar to previous reports on other filamentous fungi and yeasts (Beever and Laracy, 1986; Schuller et al, 1994; Jin et al, 2012; Babazadeh et al, 2013; Wang et al, 2016). The growth and development of mycelia fragments of Δ PfHog1 mutants were suppressed on PDA medium supplemented with 1 M NaCl; whereas WT P. fijiensis showed normal growth and development of mycelia.…”
Section: Discussionsupporting
confidence: 92%
“…For example, HOG1 pathway was found critical in regulating colonization of mouse gastrointestinal tract in Candida albicans (Prieto et al, 2014). In the entomopathogenic fungus Metarhizium acridum , MaHog1 , a member of the Hog1/Sty1/ p38 MAP-kinase gene family, has been shown to be critical for adaptation to hyper osmolarity, high temperature and oxidative stress (Jin et al, 2012). It is also an important virulence factor as disruption of MaHog1 results in reduced infectivity and growth of the fungus on its insect hosts (Jin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These central pathways in turn regulate, typically via phosphorylation, downstream effectors including transcription factors that can be either activated or repressed by the incoming signal. The transcription factors affect the expression of genes in response to the original signal phenotype seen in B. bassiana, disruption of the Mahog1 gene resulted in increased sensitivity to osmotic and oxidative stress, with a counterbalance of decreased sensitivity to cell wall perturbing reagents such as calcofluor white and Congo red (Jin et al 2012). As seen in B. bassiana, the ΔMahog1 strain displayed reduced conidial germination, appressorium formation, and virulence.…”
Section: Map Kinase Pathwaysmentioning
confidence: 96%
“…The osmoregulation MAPK pathway is well conserved in fungi. The inactivation of Hog1 orthologs increases sensitivity to osmotic stress and attenuates the virulence of Beauveria bassiana (Zhang et al 2009), Cryphonectria parasitica (Park et al 2004), Fusarium graminearum (Zheng et al 2012) and Metarhizium acridum (Jin et al 2012), and Ustilaginoidea virens (Zheng et al 2016). The osmoadaptative response of F. verticillioides is also coupled to the marked induction of FUM1 gene expression, a gene required for fumonisin biosynthesis (Marín et al 2010).…”
Section: Discussionmentioning
confidence: 99%